Triplet State Formation in Photovoltaic Blends of DPP‐Type Copolymers and PC71BM. Issue 11 (29th April 2015) - Ochsmann, Julian R.; Chandran, Deepak; Gehrig, Dominik W.; Anwar, Husna; Madathil, Pramod Kandoth; Lee, Kwang‐Sup; Laquai, Frédéric; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> The exciton dynamics in pristine films of two structurally related low‐bandgap diketopyrrolopyrrole (DPP)‐based donor–acceptor copolymers and the photophysical processes in bulk heterojunction solar cells using DPP copolymer:PC71BM blends are investigated by broadband transient absorption (TA) pump‐probe experiments covering the vis–near‐infrared spectral and fs–μs dynamic range. The experiments reveal surprisingly short exciton lifetimes in the pristine polymer films in conjunction with fast triplet state formation. An in‐depth analysis of the TA data by multivariate curve resolution analysis shows that in blends with fullerene as acceptor ultrafast exciton dissociation creates charge carriers, which then rapidly recombine on the sub‐ns timescale. Furthermore, at the carrier densities created by pulsed laser excitation the charge carrier recombination leads to a substantial population of the polymer triplet state. In fact, virtually quantitative formation of triplet states is observed on the sub‐ns timescale. However, the quantitative triplet formation on the sub‐ns timescale is not in line with the power conversion efficiencies of devices indicating that triplet state formation is an intensity‐dependent process in these blends and is reduced under solar illumination conditions, as free charge carriers can be extracted from the photoactive layer in devices.